Fundamentals and applications of lithium-ion batteries in electric drive vehicles - Jiang, Jiuchun; Zhang, Caiping (Chemist) (Singapore : John Wiley & Sons Inc., 2015)
A theoretical and technical guide to the electric vehicle lithium-ion battery management system Covers the timely topic of battery management systems for lithium batteries. After introducing the problem and basic background theory, it discusses battery modeling and state estimation. In addition to theoretical modeling it also contains practical information on charging and discharging control technology, cell equalisation and application to electric vehicles, and a discussion of the key technologies and research methods of the lithium-ion power battery management system. The author systema.
6.2 Evaluation Indexes of Battery Consistency6.3 Quantitative Evaluation of Battery Consistency; 6.4 Equalization of the Battery Pack; 6.5 Summary; References; 7 Technologies for the Design and Application of the Battery Management System; 7.1 The Functions and Architectures of a Battery Management System; 7.2 Design of the Battery Parameters Measurement Module; 7.3 Design of the Battery Equalization Management Circuit; 7.4 Data Communication; 7.5 The Logic and Safety Control; 7.6 Testing the Stability of the BMS; 7.7 Practical Examples of BMS; Index; End User License Agreement.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Electric vehicles -- Batteries; Lithium ion batteries; Electric vehicles -- Batteries; Hybrid electric vehicles -- Batteries; Lithium ion batteries; TECHNOLOGY & ENGINEERING -- Engineering (General); Electric vehicles -- Batteries; Lithium ion batteries; Electronic books